93.6k views
1 vote
Helpppppppppppppppppppppppppppppp

Helpppppppppppppppppppppppppppppp-example-1
User Red Mak
by
5.7k points

1 Answer

6 votes
Answer:
4/9

Step-by-step explanation:
For the left hand side:
log base 2 of (6x) - log base 2 of (√x) = log base 2 of (6x / √x)

Equating this to the right hand side we will get:
log base 2 of (6x / √x) = 2

Converting this into exponent form, we will get:
2^2 = 6x/√x
4 √x = 6x
4√x - 6x = 0
√x (3√x - 2) = 0
either √x = 0....> This value is rejected as the log base 2 of zero is undefined
or √x = 2/3 which means that x = 4/9

Hope this helps :)
User Igauravsehrawat
by
6.0k points